A New VISTA on combination therapy for negative checkpoint regulator blockade - Deng, Jie; Le Mercier, Isabelle; Kuta, Anna; Noelle, Randolph J. (Journal for immunotherapy of cancer, 2016)
Negative checkpoint regulators function to restrain T cell responses to maintain tolerance and limit immunopathology. However, in the setting of malignancy, these pathways work in concert to promote immune-mediate escape leading to the development of a clinically overt cancer. In the recent years, clinical trials demonstrating the efficacy of blocking antibodies against these molecules have invigorated the field of immunotherapy. In this review, we discuss the current understanding on established NCR blockade and how strategic combination therapy with anti-VISTA antibody can be used to target multiple non-redundant NCR pathways.